7 Remote maintenance cardiac rehabilitation (MAINTAIN): a protocol for a randomised feasibility study. (21st November 2022) - Denton, Francesca; Waddell, Alexander; Kite, Chris; Hesketh, Katie; Atkinson, Lou; Cocks, Matthew; Jones, Helen; Randeva, Harpal; Davenport, Nathan; Powell, Richard; Clark, Cain; Kyrou, Ioannis; et al.
Abstract : Background: Long-term adherence to exercise is often poor for people with coronary heart disease (CHD) who have completed supervised, centre-based cardiac rehabilitation. Wearable activity devices with personalised feedback may remotely support people with CHD to maintain their exercise achieved during cardiac rehabilitation (CR). Aim: The aim of this study is to assess the feasibility of a remotely prescribed, delivered and monitored CR intervention using a wearable device to support long-term adherence to exercise and physical activity during maintenance cardiac rehabilitation. Methods: After completing and being discharged from phase III CR, 30 participants with CHD, will be randomised (1:1) to an intervention (n=15) or a usual care group (n=15) in a 12-month feasibility randomised controlled trial (RCT). The intervention will comprise of an exercise consultation, personalised exercise prescription delivered via a wearable activity monitor using biometric feedback, regular monitoring via check-ins at one, three and six-months, and feedback text-messages for six-months. Participants will be assessed at baseline (following completion of CR) and at three-, six-, and 12-months post-randomisation. The primary outcome will be feasibility, including assessment of eligibility, recruitment, adherence, and acceptability. Secondary outcomes will include exercise capacity, physical activity behaviours, 10-year risk for recurrent vascular events using the SMART risk score and quality of life. Semi-structured interviews will be conducted at three-, six-, and 12-months post randomisation (and with those who drop-out) to explore the acceptability of the study intervention and procedures. A questionnaire will be offered to those who decline participation. Conclusion: The MAINTAIN study will evaluate the feasibility of conducting a future definitive multi-centre RCT testing a remotely prescribed and monitored long-term maintenance exercise programme using a wearable activity device, versus usual care, for people with CHD who have completed supervised CR.